Costos de cumplimiento de regulación ambiental con información incompleta: Aplicación a fuentes fijas del PCE de Santiago, Chile - Gaspard Clerger; Carlos Chávez; Mauricio Villena; Walter Gómez (Estudios de Economía, 2009)
– We study the cost-effectiveness of a transferable emissions permit system (TEPS) vis a vis a system of emissions standards. Our analysis includes along with abatement costs, the costs of enforcing the system to induce compliance. Further, the analysis considers complete and incomplete information. The numerical simulations are performed for the case of fixed sources operating under the Emissions Compensation Program (ECP) in Santiago, Chile. The results suggest that a TEPS is not able to induce compliance at minimum enforcement costs, but this regulatory system allow the regulator to achieve the environmental target with minimum aggregate compliance costs.
Keywords: L51; Q28; K42; K32; 330; environmental policy; cost-effectiveness; enforcement costs incomplete information; Umweltpolitik; Emissionshandel; Kosten-Wirksamkeits-Analyse; Unvollkommene Information; Santiago (Chile)